Prevalence of Epileptic Syndromes in Finland - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The prevalence of epilepsy and types of seizures and epileptic syndromes in children in the district of the Tampere University Hospital (population 175,000) and 34 surrounding rural counties was determined by a retrospective review of medical records and EEG recordings, using the latest ILAE International Classifications.